An extended user experience evaluation over time model for e-procurement system - Yusof, Norhanisha (2022)
Despite many benefits in using e-procurement, its usage remains poor due to its module complexity, lack of user-friendliness, and negative past experiences dwelt by some users while using it. Current user experience (UX) evaluation models are not developed for e-procurement systems, do not support over time measurement, and do not cover important dimensions of e-procurement. Furthermore, the qualitative and quantitative measurements in the existing models are still lacking in measurement integration methods. Therefore, this study was conducted to develop an extended UX evaluation over time model for the e-procurement system. This study was conducted in four phases: theoretical study, model development, model verification, and model validation. The theoretical study phase comprised a literature review, a questionnaire survey, a pre-interview, and an interview to synthesise the UX dimensions, criteria, and metrics, which were then used for the UX model development. The developed model was verified by academics and industry experts and subsequently analysed using the Fuzzy Delphi method. The model was later validated by e-procurement users using a UX instrument, involving 65 participants and a diary study method, involving 13 participants. Descriptive analysis, logistic regression, and Wilcoxon Signed-rank test were performed for the survey data. Meanwhile, the data collected from the diary study to capture over time user journey was analysed using thematic analysis. This study produced an extended UX evaluation over time model, its instrument and a User Journey Map (UJM). The developed model, its UX measurement instrument, and its empirical findings could contribute to the field of UX, especially in design and method of evaluation. The new UX measurement instrument will be useful for system designers and UX practitioners as a guide during the design phase. In addition, customer service personnel can use UJM to identify common complaints from the eprocurement users.